Pengembangan bahan ajar IPA terintegrasi nilai Islam untuk meningkatkan sikap dan prestasi belajar IPA siswa - Susilowati Susilowati (Jurnal Inovasi Pendidikan IPA, 2017)
Penelitian ini bertujuan untuk menghasilkan bahan ajar IPA yang terintegrasi nilai Islam, mengetahui kelayakan dan keefektifan bahan ajar yang dikembangkan untuk meningkatkan sikap dan prestasi belajar IPA. Sikap terdiri dari sikap religi dan sikap positif terhadap IPA. Metode yang digunakan dalam penelitian ini adalah Research and Development (RD) yang dikembangkan oleh Borg Gall. Teknik analisis data menggunakan gain score, independent t test, dan uji MANOVA. Bahan ajar dalam bentuk buku siswa MTs dan buku guru MTs. Penilaian produk buku siswa MTs  menurut ahli materi dan ahli media berkategori “sangat baik”. Buku guru MTs menurut ahli materi berkategori “baik” dan menurut ahli media berkategori “sangat baik”. Pembelajaran dengan menggunakan buku siswa MTs menunjukkan sikap religi meningkat tinggi (rerata gain score adalah 0,70), sikap positif terhadap IPA meningkat sedang (rerata gain score adalah 0,57), dan prestasi belajar IPA meningkat sedang (rerata gain score adalah 0,55).Kata Kunci: bahan ajar, buku siswa MTs, buku guru MTs, sikap, prestasi belajar Developing of Instructional Materials for Science Integrated with Islamic Values for Increasing Attitudes and Science Learning Achievement AbstractThe aims of the research was to develop instructional materials for science integrated with Islamic values, to determine the appropriateness and the effectiveness of the developed product  for increasing attitudes and science learning achievement. Attitudes is consist of religious attitudes and positive attitudes toward science. This research is Research and Development (R D) using Borg Gall model. Data analysis techniques using gain score, independent t-test, and MANOVA test. Instructional materials in the form of MTs student books and MTs teacher books. Product assessment of the MTs student books according to matter experts and media experts are categorized “very well”. The MTs teacher books according to matter experts are categorized “good”, and according to media experts is categorized “very well”. Learning to use student books showed that religious attitudes have risen high (the mean gain score is 0.70), positive attitudes towards science have risen middle (the mean gain score is 0.57), and science learning achievement have risen middle (the mean gain score is 0.55).Keywords: instructional material, MTs student books, MTs teacher books, attitudes, science learning achievement